La gestion de la transhumance dans la zone d’influence du parc régional du W par le programme Ecopas - Arnaud Convers; Issa Chaibou; Aurélie Binot; Dominique Dulieu (VertigO)
When the W-Park ECOPAS program started in 2001, transhumant cattle’s farming has been identified as the major issue to deal with for the implementation of conservation policies in this area. Since its creation in 1954, the park has always been used by the herders to face the lack of pastoral resources in the dry season. The conservation program implemented an approach to manage this illegal grazing inside the park, by a multi-level concentration with all stakeholders (from herders to ministers). This aims mostly the sustainable management of pastoral land tenure issues in and around the transboundary protected area.